2014
DOI: 10.1016/j.pmrj.2014.08.950
|View full text |Cite
|
Sign up to set email alerts
|

The History of the 75‐Percent Rule: Three Decades Past and an Uncertain Future

Abstract: Our story begins on July 30th, 1965, in Independence, Missouri. President Lyndon Baines Johnson is about to sign amendments to the Social Security Act: Titles 18 and 19, which will create Medicare and Medicaid. President Johnson flew to Independence to honor former President Harry S. Truman, who was too ill to travel to Washington, DC. Truman had proposed government-financed health insurance in the late 1940s, during his presidency. The large oak desk on which Johnson signed Medicare and Medicaid into law is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The 60% rule is a regulation-based entirely upon opinion. [30] There have been only 3 studies evaluating the 3-hour rule. Neither this study nor the study of Johnston and Miller [4] found that patients whose treatments are consistent with the 3-hour rule have better outcomes than patients who receive a little less therapy time than is required by the rule.…”
Section: Discussionmentioning
confidence: 99%
“…The 60% rule is a regulation-based entirely upon opinion. [30] There have been only 3 studies evaluating the 3-hour rule. Neither this study nor the study of Johnston and Miller [4] found that patients whose treatments are consistent with the 3-hour rule have better outcomes than patients who receive a little less therapy time than is required by the rule.…”
Section: Discussionmentioning
confidence: 99%
“…The three‐hour rule was originally discussed in a meeting in 1978, according to Dr. Leon Reinstein 1 . The American Academy of Physical Medicine & Rehabilitation (AAPM&R) formed a rehabilitation criteria committee in collaboration with the Peer Standards Review Organization (PSRO) to come up with criteria for admission to a rehabilitation unit.…”
Section: History Of the “Three‐hour Rule”mentioning
confidence: 99%
“…1 The American Academy of Physical Medicine & Rehabilitation (AAPM&R) formed a rehabilitation criteria committee in collaboration with the Peer Standards Review Organization (PSRO) to come up with criteria for admission to a rehabilitation unit. The criteria that they initially identified included: (1) The patient was medically stable, (2) there was a reasonable expectation that the patient would experience significant functional improvement in a reasonable period of time, (3) the patient was expected to be able to tolerate and participate in 3 hours of combined PT, OT, speech therapy (ST), and/or prosthetic/orthotic services daily. The committee was also asked to come up with the seven most common diagnoses that were treated in the rehab program, and the Health Care Financing Administration (HCFA) 75% rule soon followed.…”
Section: History Of the "Three-hour Rule"mentioning
confidence: 99%
See 1 more Smart Citation
“…Medicare's “75% rule” stipulated that, to qualify as an IRF, 75% of a facility's patient census must be admitted with 1 of 13 diagnoses, including hip fracture, polyarticular rheumatoid arthritis, and severe osteoarthritis [6] . In 2005, this was amended to a revised 60% rule, and consequently, more of these patients were diverged from the IRF to the SNF for post-TJA care [7] .…”
Section: Introductionmentioning
confidence: 99%